2003
DOI: 10.1111/j.1834-7819.2003.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of enamel subsurface lesions in situ by sugar‐free lozenges containing casein phosphopeptideamorphous calcium phosphate

Abstract: Background:The anticariogenic potential of casein phosphopeptide-amorphous calcium phosphate nanocomplexes (CPP-ACP) has been demonstrated using laboratory, animal and human in situ caries models. The aim of this study was to determine the effect of CPP-ACP incorporation into a sugar-free lozenge (pressed mint tablet) on enamel remineralization in a human in situ model. Methods:The study utilized a double-blind, randomized, cross-over design with four treatments: (i) a lozenge containing 56.4mg (3 per cent w/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 9 publications
3
88
0
4
Order By: Relevance
“…12,13,15,27 It has been proposed that the anticariogenic mechanism of CPP-ACP is due to localization of ACP at the tooth surface which then buffers the free calcium and phosphate ion activities, thereby helping to maintain a state of supersaturation with respect to the enamel, so depressing demineralization and promoting remineralization. 8 Several studies have shown that higher concentration of CPP-ACP elicit higher remineralization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13,15,27 It has been proposed that the anticariogenic mechanism of CPP-ACP is due to localization of ACP at the tooth surface which then buffers the free calcium and phosphate ion activities, thereby helping to maintain a state of supersaturation with respect to the enamel, so depressing demineralization and promoting remineralization. 8 Several studies have shown that higher concentration of CPP-ACP elicit higher remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 Furthermore, the remineralized enamel was generally more resistant to decalcification than untreated enamel. 15 The fact that this effect of remineralization of enamel was not confined to chewing gums as a vehicle was demonstrated by Cai et al 13 In clinical trials in patients with severe xerostomia, CPP-ACP in a mouthrinse revealed positive results in terms of caries prevention 16 and mouth moistening. 17 In vitro, CPP-ACP stabilized calcium phosphate solutions have been shown to remineralize subsurface lesions in human third molar enamel.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 Daily use of casein phosphopeptide (CPP)-amorphous calcium phosphate (ACP) has been shown to increase enamel remineralization, and mineralization of artificial subsurface enamel lesions increased more than 78% compared to control samples. 11,12 CPP stabilized ACP, and CPP-ACP clusters formed. 13 These CPP-ACP clusters increase the plaque calcium and phosphate levels and remineralize the enamel.…”
Section: Introductionmentioning
confidence: 99%
“…While used with chewing gums and lozenges which contained CPP-ACP for 14 days increased the enamel remineralization. 12,13 This study objectives were to count the amount of Streptococcus mutans in the plaque isolate before and after application of CPP-ACP paste topically in children teeth, in order to find any significance of growth amount of Streptococcus mutans before and after application of CPP-ACP paste topically in children teeth.…”
Section: Introductionmentioning
confidence: 99%